Traditions of German Expressionism in the Cinematography of the Second Half of the 20th – Early 21st Centuries - E. A. Radaeva (Концепт: философия, религия, культура, 2022)
The subject of this study is the influence of the traditions of German expressionism on modern cinema, primarily the horror genre. The relevance of this work is due to the need to study the genesis of modern trends in one of the most popular types of art and its popular genres in the context of cultural history in terms of allusions and reminiscences, traditions and innovation. In order to prove that the traditions of expressionism are clearly traced to this day and promise to be quite productive in the long run, as well as to trace the nature of their presence in the history of the film industry, in line with the culturological approach, the method of comparative historical and historical situational analysis, as well as content analysis was mainly used regarding cinematography of the period under consideration. The scientific novelty of the work lies in the very prism of the study and its object — the films of 2021–2022 were considered in terms of traditions of expressionist aesthetics; in addition, the article presents a slightly different view on the masterpieces that have become classics of the cinema of the 20th century. As a result, it was revealed that the expressionist concept of man and the world is strong in the artistic world of cinema art of this period. The methods of German filmmakers of the beginning of the previous century were continued in a somewhat modified form at the level of the play of light and shadow, framing, the figurative system itself (vampires, homunculi, ghosts), mechanistic acting, sinister paraphernalia, and deceitful details. The common denominator of foreign and domestic films of all the genres and subgenres considered in the article was the use of a special musical setting — music that originates from the new Viennese school (in other words, musical expressionism), which also confirms the theory put forward.